31 days before your CCNA exam a day-by-day review guide for the CCNA 200-301 certification exam - Johnson, Allan 1962- (Cisco Press, 2025)
31 Days Before Your CCNA Exam: A Day-By-Day Review Guide for the CCNA 200-301 Certification Exam Second Edition is the friendliest, most practical way to understand the CCNA Routing and Switching certification process; to commit to taking your CCNA 200-301 exam; and to finish your preparation using a variety of primary and supplemental study resources. Thoroughly updated for the current exam, this portable guide offers a complete day-by-day plan for what and how to study. From the basics of switch configuration and IP addressing through modern cloud, virtualization, SDN, SDA, and network automation concepts, youll find it here. Each day breaks down an exam topic into a short, easy-to-review summary, with Daily Study Resource quick-references pointing to deeper treatments elsewhere. Sign up for your exam now, and use this day-by-day guide and checklist to organize, prepare, review, and succeed!
Includes index. - Description based on print version record
Keywords: Electronic data processing personnel -- Certification; Computer networks -- Study guides -- Examinations